CORRELATION ANALYSIS OF MEASUREMENT RESULTS USING THE LIGHT WEIGHT DEFLECTOMETER (LWD) TOOL AGAINST THE FALLING WEIGHT DEFLECTOMETER (FWD) TOOL - Novriyani, Irma
Currently in Indonesia, a tool that can measure flexible pavement characteristics on roads with low traffic volume has been developed, namely the Light Weight Deflectometer. This tool is able to read deflections without damaging the existing pavement or non-destructive tests, has good mobility and is more affordable than testing deflections with other tools. In Indonesia, the use of the LWD tool as a tool for retrieving deflection data which is then used for the design of overlay requirements is still quite rare because the FWD or Falling Weight Deflectometer tool is more commonly used on roads with low and medium traffic volumes. In order to increase the use of LWD, it is necessary to analyze the correlation between the data from the LWD and FWD tools of the Directorate of Road and Bridge Engineering, both using a deflection bowl and an analysis of the need for overlays aimed at road maintenance. Deflection data was collected at 18 points on the Alusan Laboratory Road section of the Directorate of Road and Bridge Engineering using LWD and FWD tools owned by the Directorate of Road and Bridge Engineering. From the research conducted, it was found that the correlation of D300, D600, BLI, and MLI between LWD and FWD data had a good correlation level, but from the results of the overlay needs analysis it was found that the overlay requirement from the LWD deflection data was smaller than the overlay requirement from the FWD data. This proves that LWD utilization is used to detect pavement damage for maintenance purposes, not for deflection measurements which are then used for overlay design.